Effects of postural-control training with different sensory reweightings in a patient with body lateropulsion: a single-subject design study. - Nakamura, Junji; Nishimae, Takuma; Uchisawa, Hidekazu; Okada, Yohei; Shiozaki, Tomoyuki; Tanaka, Hiroaki; Ueta, Kozo; Fujita, Daiki; Tsujimoto, Naohide; Ikuno, Koki; Shomoto, Koji (Physiotherapy Theory & Practice, 2024)
Introduction: Body lateropulsion (BL) is an active lateral tilt of the body during standing or walking that is thought to be affected by a lesion of the vestibulospinal tract (VST) and the subjective visual vertical (SVV) tilt. Interventions for BL have not been established. Objective: We examined the effects of postural-control training with different sensory reweighting on standing postural control in a patient with BL. Methods: The patient had BL to the left when standing or walking due to a left-side medullary and cerebellar infarct. This study was a single-subject A-B design with follow-up: Phase A was postural-control training with visual feedback; phase B provided reweighting plantar somatosensory information. Postural control, VST excitability, and SVV were measured. Results: At baseline and phase A, the patient could not stand with eyes-closed on a rubber mat, but became able to stand in phase B. The mediolateral center of pressure (COP) position did not change significantly, but the COP velocity decreased significantly during phase B and the follow-up on the firm surface. VST excitability was lower on the BL versus the non-BL side, and the SVV deviated to the right throughout the study. Conclusion: Postural-control training with reweighting somatosensory information might improve postural control in a patient with BL.